PREGNANCY IN THE RUBBLE AFTER CESAREAN SECTION - FOLLOWING THE INTERNATIONAL CLASSIFICATION - Игорь Сергеевич Захаров; Вадим Гельевич Мозес; Светлана Николаевна Болотова; Тамара Николаевна Демьянова; Марина Сергеевна Рыкова; Юлия Валерьевна Васютинская (The Publishing House Medicine and Enlightenment, 2018)
The article presents a clinical case of a fairly rare pathology of the gestational period, an ectopic pregnancy localized in the scar area after a previous cesarean section. The complexity of timely diagnosis of this complication is demonstrated.